Association between fat mass index and fat-free mass index values and cardiovascular risk in adolescents - Patrícia Morais de Oliveira; Fabiana Almeida da Silva; Renata Maria Souza Oliveira; Larissa Loures Mendes; Michele Pereira Netto; Ana Paula Carlos Cândido (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To describe the association between fat mass index and fat-free mass index values and factors associated with cardiovascular risk in adolescents in the city of Juiz de Fora, Minas Gerais. Methods: Cross-sectional study was with 403 adolescents aged 10-14 years, from public and private schools. Anthropometric, clinical, and biochemical measurements were obtained, as well as self-reported time spent performing physical exercises, sedentary activities and sexual maturation stage. Results: Regarding the nutritional status, 66.5% of the adolescents had normal weight, 19.9% were overweight and 10.2% were obese. For both genders, the fat mass index was higher in adolescents who had high serum triglycerides, body mass index and waist circumference. Conclusions: Adolescents who had anthropometric, clinical and biochemical characteristics considered to be at risk for the development of cardiovascular disease had higher values of fat mass index. Different methodologies for the assessment of body composition make health promotion and disease prevention more effective.